The Physical and Chemical Properties of the ρ Ophiuchi A Dense Core - Chen, Yu-Ching; Hirano, Naomi (The Astrophysical journal, 2018)
The physical and chemical properties of the ρ Ophiuchi A core were studied using 1.3 mm continuum and molecular lines such as C 18 O, C 17 O, CH 3 OH, and H 2 CO observed with the Submillimeter Array. The continuum and C 18 O data were combined with the single-dish data obtained with the IRAM 30 m telescope and the James Clerk Maxwell Telescope, respectively. The combined 1.3 mm continuum map reveals three major sources, SM1, SM1N, and VLA 1623, embedded in the extended emission running along the north–south direction, and two additional compact condensations in the continuum ridge connecting SM1 and VLA 1623. The spatial distribution of the C 18 O emission is significantly different from that of the continuum emission; the C 18 O emission is enhanced at the eastern and western edges of the continuum ridge, with its peak brightness temperature of 40–50 K. This supports the picture that the ρ -Oph A core is heated externally from the nearby stars Oph S1 and HD 147889. In contrast, the C 18 O intensity is lower than 15–20 K at the center of the ridge, where the continuum emission is bright. The C 18 O abundance decreases inside the ridge and shows anticorrelation with the N 2 H + abundance. However, both C 18 O and N 2 H + show strong depletion at the Class 0 protostar VLA 1623, implying that the dense gas surrounding VLA 1623 is colder than the freeze-out temperature of N 2 . The blue- and redshifted components of CH 3 OH and H 2 CO lines are seen at SM1, suggesting outflow activity of an embedded source in SM1, although the spatial distributions do not show clear bipolarity.